2022
DOI: 10.1002/srin.202200266
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behavior and Longevity Technologies of Refractory Linings in Blast Furnaces for Ironmaking: A Review

Abstract: Erosion of the refractory materials in blast furnaces (BFs) greatly limits their campaign life, which seriously reduces the economic benefits of iron and steel plants and endangers workers. Therefore, it is important to detect and monitor the erosion process of refractory materials in the BF hearth. In this review, the mechanisms of physical damage, chemical corrosion, and mechanical erosion of BF hearths during BF operation are analyzed and summarized. In addition, the effects of hearth structure, refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Table 2 displays some fundamental physical properties. In comparison with conventional carbon brick, the apparent porosity is a little bit lower, 10.9%; the bulk density is larger, 2.98 g/cm 3 ; the average pore diameter is greater, 0.238 mm; the pore volume (<1 mm) is relatively lower, 80.44%; and the compressive strength (room temperature) is higher, 78.4 MPa, respectively [20,21].…”
Section: Materials Preparationmentioning
confidence: 86%
See 2 more Smart Citations
“…Table 2 displays some fundamental physical properties. In comparison with conventional carbon brick, the apparent porosity is a little bit lower, 10.9%; the bulk density is larger, 2.98 g/cm 3 ; the average pore diameter is greater, 0.238 mm; the pore volume (<1 mm) is relatively lower, 80.44%; and the compressive strength (room temperature) is higher, 78.4 MPa, respectively [20,21].…”
Section: Materials Preparationmentioning
confidence: 86%
“…Apparent porosity, % 10.9 Bulk density, g/cm 3 2.98 Average pore diameter, mm 0.238 Pore volume (<1 mm), % 80.44 Compressive strength (Room temperature), MPa 78.4 samples of 346 mm in length, 150 mm in width and 98mm in height for thermal conductivity measurements, some powders for chemical composition analysis and X-ray diffraction (XRD) (Rigku SmartLab, Japan) detection after ground in agate mortar for 30 min, and some regular lumpy specimens for scanning electron microscope and energy dispersive spectrometer (SEM-EDS) (FEI Quanta 250, Holland) detection.…”
Section: Index Valuementioning
confidence: 99%
See 1 more Smart Citation
“…[ 3–5 ] It was found that a certain part of the hearth refractory was eroded, the molten iron would be enriched in the inner layer of this part, and a brittle layer appeared in the outer layer of the molten iron enrichment area. [ 6–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Hearth activity plays a crucial role in achieving high efficiency, high quality, low consumption, and long life in BF production, which directly affects the running and first-generation BF lifespan. [5][6][7][8][9][10] In recent years, BF-intensified smelting has become common, and the problem of hearth activity in BFs has attracted increasing attention; however, there has been little research on the quantitative evaluation of hearth activity. The traditional model for hearth activity evaluation is primarily based on mechanistic research.…”
Section: Introductionmentioning
confidence: 99%